The Fate of Political Scientists in Europe From Myth to Action - Capano, Giliberto (Springer Nature, 2023)
This open access book offers a systematic survey of the attitudes and values of European political scientists. It builds a structural interpretation based on empirical data, as well as offering reflections on the future structure of the discipline. In the middle of a delicate phase of changes marked by the effects of pandemic and the war in Ukraine, we need to pay attention to the factors that are affecting not only the 'objects' of Political Science as a discipline but also its interactions with the world around it. First, this book asks to what extent the work of European political scientists is impacted by the current change. Second, their attitudes and predisposition about the future goals of the discipline are analysed. In the final chapter, the authors seek to understand to what extent a diffuse but still not completely institutionalized academic discipline will be able to produce a comprehensive impact around the European society, in order to be more visible and effective in policy making and policy processes.